Comparison of P-53, Ki-67 and Cd-10 Expression Between Fibroadenoma, Benign Phyllodes Tumor and Malignant Phyllodes Tumor - Sukumar, Challa; Yadav, Shakti Kumar; Singh, Garima; Singh, Sompal; Sarin, Namrata (Annals of Pathology and Laboratory Medicine, 2021)
Background: Fibroepithelial tumors of the breast are a heterogeneous group of biphasic lesions comprising of an epithelial component and a quantitatively predominant mesenchymal component. These are classified into two major categories: Fibroadenoma and phyllodes tumor (PT). Phyllodes tumors are classified into benign, borderline and malignant grade categories based on histological parameters. Methods: An analytical-cross sectional study was conducted in the Department of Pathology, Hindu Rao Hospital, Delhi-110007 from November 2016 to December 2018. Total 50 cases were included in the study comprising of 30 cases of fibroadenoma, 15 cases of benign phyllodes tumor and 5 cases of malignant phyllodes tumor. All specimens were fixed in 10% buffered formalin. Tissue were processed and embedded in paraffin. The sections were stained with hematoxylin and eosin (H&E) to study the histopathological section. Immunostaining using CD-10, Ki-67 and p53 antibodies was done in all cases. Result: Among fibroadenoma cases only 3.33% showed positive CD-10 expression and 96.66% were negative. CD-10 expression was positive in 26.67% cases of benign phyllodes while 73.33 showed negative expression. 40% malignant phyllodes cases showed positive CD-10 expression and 60% showed negative CD-10 expression. CD-10 expression was significantly higher in benign phyllodes (p value = 0.019) and malignant phyllodes (p value 0.007) group as compared to fibroadenoma. P-53 expression in epithelium was seen in 56% of fibroadenoma and 26% of benign phyllodes cases, while all cases of malignant phyllodes tumor show negative P-53 expression. The stromal expression of P-53 was significantly higher in malignant phyllodes as compared to fibroadenoma and benign phyllodes tumor. Stromal expression of Ki-67 was significantly higher in malignant phyllodes as compared to benign phyllodes and fibroadenoma. Epithelial expression of Ki-67 was negative in all malignant phyllodes cases while positive epithelial Ki-67 expression was seen in 56% of fibroadenoma and 33% of benign phyllodes tumor. Conclusion: Both Ki-67 and P-53 showed a significantly increasing expression from fibroadenoma to benign phyllodes to malignant phyllodes tumor. The difference in expression of CD-10 was insignificant among fibroadenoma, benign phyllodes and malignant phyllodes tumor.